2011
DOI: 10.1002/ca.22005
|View full text |Cite
|
Sign up to set email alerts
|

Can clinical examination cause a Stener lesion in patients with skier's thumb?: A cadaveric study

Abstract: Approximately one-third of all injuries of the upper limb and 7% of all injuries in skiing affect the ulnar collateral ligaments of the thumb metacarpophalangeal joint (skier's thumb). In some patients the collateral ligaments are displaced proximally over the adductor aponeurosis, resulting in a so-called Stener lesion. In these cases surgical treatment is indicated. We hypothesized that a Stener lesion could be provoked by clinical stability testing in patients with a skiers thumb and performed a cadaveric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…The order of sectioning the tissues, pUCL, aUCL, and then the aponeurosis, reproduced the sequence of injury in traumatic events. 10,16) Similar to the finding of Adler et al, we were unable to create a Stener lesion after complete sectioning of the UCL at 0°and 30° of flexion with no rotation. 16) We also did not create a Stener lesion with supination or pronation with intact overlying fascia.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The order of sectioning the tissues, pUCL, aUCL, and then the aponeurosis, reproduced the sequence of injury in traumatic events. 10,16) Similar to the finding of Adler et al, we were unable to create a Stener lesion after complete sectioning of the UCL at 0°and 30° of flexion with no rotation. 16) We also did not create a Stener lesion with supination or pronation with intact overlying fascia.…”
Section: Discussionsupporting
confidence: 83%
“…10,16) Similar to the finding of Adler et al, we were unable to create a Stener lesion after complete sectioning of the UCL at 0°and 30° of flexion with no rotation. 16) We also did not create a Stener lesion with supination or pronation with intact overlying fascia. Unlike the study by Adler, we used fresh frozen cadavers rather than preserved specimens.…”
Section: Discussionsupporting
confidence: 83%
“…Other authors argue that, in the case of associated undisplaced fractures, the injury force is always greater than the force applied during clinical testing, thus allaying any fear of displacement. A recent cadaver study concluded that correctly performed stress test examinations do not cause Stener lesions. Thirkannad and Wolff described the “Two Fleck Sign”, wherein two bony fragments are present: one of them is usually obvious and denotes an undisplaced avulsion fracture whereas the other, which is frequently missed during initial X‐ray evaluation, denotes a Stener lesion.…”
Section: Diagnosismentioning
confidence: 99%
“…However, if the initial trauma was insufficient to cause a dislocation, the thought is that the strength used to test the thumb clinically is not enough to cause one [12]. Also, in a study with cadavers [13], a Stener lesion could not be caused by a correct clinical examination.…”
Section: Reviewmentioning
confidence: 99%